UPAYA PENINGKATAN MOTIVASI DAN PRESTASI BELAJAR AKUNTANSI MELALUI PENERAPAN TGT BERBANTU MEDIA KOKAMI DI SMK HARAPAN - Dara, Avni Laksmi; Santoso, Sigit; Muchsini, Binti (Tata Arta : Jurnal Pendidikan Akuntansi, 2016)
ABSTRACTThe objective of this research is to improve the learning motivation and achievement in Accounting through the application of the mysterious card box-assisted teams games tournament (TGT) learning model at Harapan Vocational High School. This research used the classroom action research with two cycles. Each cycle consisted of four phases, namely: planning, implementation, observation, and reflection. The subjects of the research were the students as many as 36 in Grade X Accounting 2 of Harapan Vocational High School. The data of research used were the qualitative and quantitative ones, which were obtained from the teacher, the students, and documents. The questionnaire and test instruments were respectively validated by using the construct validity and the content validity. They were collected through observation, test, questionnaire, and documentation. The quantitative data were analyzed by using the statistical descriptive comparative analysis, and the qualitative ones were analyzed by using the critical analysis. The successfulness indicators of this research were the studentsâ learning motivation reached at least 75% and the percentage of the students who fulfilled the minimum learning completeness was 75% with the score of at least 78. The result of research shows that the application of the mysterious card box-assisted TGT learning model can improve (1) the studentsâ learning motivation as indicated by the improvement the average learning motivation from 68.27% in Cycle I to 78.09% in Cycle II; (2) the learning achievement in Accounting on the Transaction Document Management as indicated by the improvement of learning achievement in Accounting on the cognitive domain in which the percentage of the students who fulfilled the minimum learning completeness increased from 69.44% in Cycle I to 80.56% in Cycle II. Thus, the application of the mysterious card box-assisted TGT learning model can improve the learning motivation and accounting achievement.Keywords: Mysterious card box, learning motivation, learning achievement,Â  teams games tournamentÂ ABSTRAKPenelitian ini bertujuan untuk meningkatkan motivasi dan prestasi belajar akuntansi melalui penerapan metode Teams Games Tournament (TGT) berbantu media kokami. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilakukan dalam dua siklus. Setiap siklus terdiri atas empat tahap yakni perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian adalah siswa kelas X Akuntansi 2 SMK Harapan* yang berjumlah 36 siswa. Data yang digunakan dalam penelitian ini adalah data kuantitatif dan kualitatif. Sumber data berasal dari guru, siswa, dan dokumen. Teknik pengumpulan data yang digunakan adalah observasi, tes, angket, dan dokumentasi. Validitas instrumen angket menggunakan validitas konstrak, sedangkan instrumen tes menggunakan validitas isi. Analisis data yang digunakan adalah statistik deskriptif komparatif untuk data kuantitatif dan analisis kritis untuk data kualitatif. Indikator keberhasilan dalam penelitian ini apabila motivasi belajar minimal mencapai 75% dan prestasi belajar minimal mencapai 75% dengan nilai KKM 78. Hasil penelitian menunjukkan bahwa penerapan metode Teams Games Tournament (TGT) berbantu media kokami dapat meningkatkan: 1) motivasi belajar. Hal ini ditunjukkan melalui peningkatan rata-rata motivasi belajar dari siklus I sebesar 68,01% menjadi 78,09% pada siklus II; 2) prestasi belajar akuntansi pada SK Mengelola Dokumen Transaksi. Peningkatan prestasi belajar akuntansi ranah kognitif meningkat pada siklus I dari 69,44% siswa yang mencapai nilai tuntas menjadi 80,56% siswa yang mencapai nilai tuntas pada siklus II. Simpulan penelitian ini adalah penerapan metode Teams Games Tournament (TGT) berbantu media kokami dapat meningkatkan motivasi dan prestasi belajar akuntansi.Kata kunci: Kokami, motivasi belajar, prestasi belajar, teams games tournament.*Nama instansi disamarkan